2019
DOI: 10.1029/2019jb017536
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Picking Seismic Arrival Times

Abstract: Arrival times of seismic phases contribute substantially to the study of the inner working of the Earth. Despite great advances in seismic data collection, the usage of seismic arrival times is still insufficient because of the overload manual picking tasks for human experts. In this work we employ a deep-learning method (PickNet) to automatically pick much more P and S wave arrival times of local earthquakes with a picking accuracy close to that by human experts, which can be used directly to determine seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 53 publications
0
66
0
Order By: Relevance
“… Model μ σ Pr Re F1 MAE MAPE Training data Training size Ref . EQTransformer 0.00 0.11 0.99 0.96 0.98 0.01 0.00 Global 1.2M This Study PhaseNet −0.02 0.11 0.96 0.93 0.94 0.09 0.01 North California 780K 8 GPD 0.03 0.14 0.81 0.83 0.82 0.10 0.01 South California 4.5M 10 PickNet 0.08 0.17 0.75 0.75 0.75 0.10 0.03 Japan 740K 2 PpkNet 0.02 0.15 1.00 0.91 0.95 0.10 1.85 Japan 30K 5 Yews −0.02 0.13 0.83 0.55 0.66 0.11 0.01 Taiwan 1.4M 4 Kurtosis −0.10 0.13 0.89 0.39 0.55 0.11 0.01 17 FilterPicker ...…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“… Model μ σ Pr Re F1 MAE MAPE Training data Training size Ref . EQTransformer 0.00 0.11 0.99 0.96 0.98 0.01 0.00 Global 1.2M This Study PhaseNet −0.02 0.11 0.96 0.93 0.94 0.09 0.01 North California 780K 8 GPD 0.03 0.14 0.81 0.83 0.82 0.10 0.01 South California 4.5M 10 PickNet 0.08 0.17 0.75 0.75 0.75 0.10 0.03 Japan 740K 2 PpkNet 0.02 0.15 1.00 0.91 0.95 0.10 1.85 Japan 30K 5 Yews −0.02 0.13 0.83 0.55 0.66 0.11 0.01 Taiwan 1.4M 4 Kurtosis −0.10 0.13 0.89 0.39 0.55 0.11 0.01 17 FilterPicker ...…”
Section: Resultsmentioning
confidence: 95%
“…We now compare the picking performance with five deep-learning (PhaseNet 8 , GPD 10 , PpkNet 5 , Yews 4 , PickNet 2 ) (Supplementary Fig. 9 ) and three traditional (Kurtosis 17 , FilterPicker 18 , and AIC 19 ) (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies, machine-learning phase pickers have shown promise in both picking efficiency and picking accuracy (e.g., Ross et al, 2018;Wang et al, 2019;Zhu & Beroza, 2019). However, the precision and resolution of earthquake locations determined from those machine-learning picks have not been well studied.…”
Section: Discussionmentioning
confidence: 99%